A novel LC–MS method using collagen marker peptides for species identification of glue applicable to samples with multiple animal origins - Yuki Kumazawa; Yuki Taga; Miho Takashima; Shunji Hattori (Heritage Science, 2018)
Abstract Animal glues derived from collagen-rich tissue are widely used as adhesives and binders in artworks. Identification of the animal source of glue is important not only to understand the artistic technique and historical background, but also to conduct appropriate treatment for restoration and conservation of artworks. Recently, mass spectrometric approaches have been used for species identification of glue. However, it appears that the existing methods were not applied to samples containing multiple animal sources, and the range of target species has been limited because of incomplete sequence information of collagen in public databases. In the present study, we established a novel method for discrimination of glues from eight animals applicable to samples with multiple animal origins. Trypsin-digested glue samples were analyzed by LC–MS in multiple reaction monitoring mode, and the animal source was determined based on the detection patterns of 12 type I collagen-derived marker peptides. Using the database-independent method, we successfully identified the animal source of commercial products and found the declared species for some glues to be incorrect. In addition, some products were identified to contain two different animal origins. Relative abundance of the animal origins in several impure glues was estimated using the marker peptides, which helped to speculate the reason for the detection of multiple species. We analyzed a painting (The Harvest by Camille Pissarro, 1882) and clarified that glues used in the ground and size layers of the canvas were derived from cattle (~ 65%) and sheep (~ 35%).